Teledentistry and mHealth for Promotion and Prevention of Oral Health: A Systematic Review and Meta-analysis. (August 2021) - Fernández, C.E.; Maturana, C.A.; Coloma, S.I.; Carrasco-Labra, A.; Giacaman, R.A.
The dental profession has experienced a dramatic acceleration in the use of communication systems and information-based technologies over recent years, originating new paradigms for the prevention and promotion of oral health. The purpose of this systematic review was to determine the effect of teledentistry-based (telematic) strategies, reported in randomized controlled trials and quasi-randomized trials, with a focus on oral health prevention and promotion–related outcomes in patients of all ages. We searched Medline via PubMed, SCOPUS, and Web of Science from inception until August 2020, regardless of the language of publication. We selected studies for inclusion and conducted data extraction, assessed risk of bias (Cochrane tool), and evaluated the certainty of the evidence (GRADE approach) in duplicate and independently. Out of 898 potentially eligible references, we selected 43 for full-text screening, of which 19 studies proved eligible: 18 randomized controlled trials and 1 quasi-randomized study. Virtual interventions were mostly asynchronous via apps ( n = 9), text messages ( n = 9), or computer-aided learning ( n = 1). The use of teledentistry as compared with conventional strategies may result in a large reduction in the plaque index (standardized mean difference, −1.18; 95% CI, −1.54 to −0.82; I 2 = 92%; low certainty) and will likely result in a large reduction in the gingival index (standardized mean difference, −2.17; 95% CI, −3.15 to −1.19; I 2 = 97%; moderate certainty) and in the incidence of white spot lesions (risk ratio, 0.48; 95% CI, 0.35 to 0.66; I 2 = 0%; moderate certainty), with an increased effect over time. Evidence suggests that teledentistry, particularly mHealth (messages and apps), is a promising clinical tool for preventing and promoting oral health, especially under the accelerated virtualization of dentistry. Future studies should include a broader spectrum of the population, including adults and elders, to better inform policy and implementation of teledentistry (PROSPERO: CRD42020192685).